Application Of A Web-Based Information System in The Institution Of Research, Community Service, and Innovation (Lp2mi) IKesT Muhammadiyah Palembang - Arif Fadillah; Fadhil Ramadhan (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
Background: Technology is something that cannot be separated in this modern era. With the emergence of technology, it can facilitate the operational activities of a higher education institution in processing data quickly and precisely. The research, community service and innovation institute (LP2MI) at IKesT Muhammadiyah Palembang in making reports and managing data currently has not implemented an application, so that the data collection process is not effective and efficient. Purpose: The purpose of this research is to be able to help LP2MI IKesT Muhammadiyah Palembang in processing and reporting of data quickly, precisely and accurately. Research Methods: This study uses data collection techniques using qualitative methods. Namely by interviews and observations as well as with the waterfall design. Results: The results of the research are making